A Study on the Application of Chinese Linguistic Landscape in Task-Based Language Teaching: 论文题目任务试教学法中汉语语言景观应用研究 - Yifan Hu; Cicik Arista (Published by Confucius Institute UNS, 2025)
This study explores the integration of linguistic landscape into international Chinese language teaching through a task-based instructional approach. Second-year Chinese majors at Universitas Negeri Surabaya (HSK Level 2-3) were guided to observe, collect, and analyze authentic Chinese signage in Surabaya, producing group reports and presentations. Data from students’ documentation and interviews were analyzed qualitatively. The findings show that using real linguistic landscape resources effectively enhances learners’ character recognition, vocabulary development, and multilingual awareness, while its impact on grammar remains limited due to proficiency level. Overall, the study demonstrates that incorporating local linguistic landscape into task-based teaching provides meaningful input, increases cultural sensitivity, and supports learner autonomy in second-language learning.